Validity of Biological Father As Marriage Guardian Against Syubhat's Son - Mushthafa, Mushthafa; AN, Rusydi; Nurliana, Nurliana (Sekolah Tinggi Agama Islam Solok Nan Indah, 2023)
This study aims to understand and find out how the marriage guardian is determined for children born as a result of a relationship Wath'i syubhat, be it a relationship Wath'i syubhat because of the contract and/or relationship Wath'i syubhat due to actions, as well as the legal consequences of having a biological father who is the child's marital guardian suspicious. Indeed, in Law No. 1 of 1974 concerning Marriage in article 43 paragraph (1) it is explained that: